Evaluation of the Medicine Logistics Management System at Public Health Centers - Haviana, Evan; Hardi, Yuni; Aini, Nurul (Public Health and Safety International Journal, 2025)
This study aims to evaluate the medicine logistics management system at Puskesmas x, Batam City, focusing on three key components: medicine distribution, ordering time and Reorder Point (ROP), and medicine disposal. A qualitative research approach was employed, with data collected through in-depth interviews, observations, and document reviews conducted between March and April 2025. The key informants included the pharmacist-in-charge and pharmacy technicians.The results indicate that medicine distribution follows a structured procedure, applying the First Expired First Out (FEFO) and First In First Out (FIFO) principles to maintain quality and minimize waste. The ROP method is integrated into a computerized system, enabling timely procurement when stock levels reach the minimum threshold. Medicine disposal is conducted according to the Standard Operating Procedure (SOP), with expired medicines identified, documented, and either returned to the Batam City Health Office or destroyed on-site.Although the system largely complies with the Standar Pelayanan Kefarmasian di Puskesmas, challenges remain, including procurement delays due to central warehouse shortages and occasional expired stock. Strengthening coordination with the Health Office, improving demand forecasting, and establishing contingency procurement strategies are recommended to enhance efficiency and ensure uninterrupted medicine availability.